Gastric hamartomatous inverted polyp: Report of three cases with a review of the endoscopic and clinicopathological features. Issue 1 (4th January 2023) - Ohtsu, Takuya; Takahashi, Yu; Tokuhara, Mitsuo; Tahara, Tomomitsu; Ishida, Mitsuaki; Miyasaka, Chika; Tsuta, Koji; Naganuma, Makoto
Abstract: Objectives: A gastric hamartomatous inverted polyp (GHIP) is a rare submucosal tumor characterized histopathologically by a submucosal inverted proliferation of cystically dilated hyperplastic gastric glands. Only 42 GHIPs have been reported in English literature. Few GHIPs have been reported to accompany adenocarcinomas. We reported on three patients with a GHIP and reviewed the clinicopathological and endoscopic features of GHIPs. Methods: This study included two men and one woman with a GHIP. The endoscopic, histopathological, and immunohistochemical features of the endoscopically resected specimens were analyzed. A gene mutation analysis was also performed. Results: All the tumors were located in the body of the stomach, with a median size of 20 mm. Two tumors were sessile, and the remaining tumor had a pedunculated appearance. The overlying mucosa mainly appeared normal but was reddish in one tumor. The histopathological examination of the tumors revealed a well‐circumscribed and lobular submucosal proliferation of cystically dilated hyperplastic glands. The immunohistochemical analysis revealed that the MUC5AC‐positive foveolar epithelium was located in the center, and MUC6‐positive pseudo‐pyloric or pepsinogen‐I and H + /K + ATPase‐positive fundic‐type glands were located at the periphery of two tumors. No carcinomatous components were noted in any of the tumors. Moreover, no significant mutations in oncogenes or tumor suppressor genes were noted. Conclusions: Our review revealed that approximately three fourths of GHIP cases showed an submucosal tumor‐like feature, whereas endoscopic features, including the endoscopic ultrasonography findings, were not characteristic. Because an endoscopic diagnosis of a GHIP may be difficult, complete endoscopic resection may be required for a pathological diagnosis.